Caracterización de Bacillus subtilis y B. pumilus con actividad antagónica en cepas Shigatoxigénicas de Escherichia coli. Utilidad para el control de la contaminación en reservorios - Blanco Crivelli, Ximena (2023)
Shiga toxin-producing Escherichia coli (STEC) is a zoonotic pathogen belonging to the Enterobacteriaceae family, commonly associated with hemolytic uremic syndrome (HUS). HUS primarily affects infants and young children, potentially causing renal pathology or leading to patient death. Cattle are the main reservoir of STEC. To reduce the burden of STEC in meat, several pre-slaughter and post-slaughter control strategies have been established. \nIn this study, six native strains of Bacillus spp. were evaluated, pre-selected for their antagonistic activity against STEC. Biochemical identification of the strains was performed, showing phenotypic characteristics consistent with the Bacillus genus. \nNotably, these strains exhibited growth at acidic pH (4.5) and tolerance to 40% bile. The strains were identified as B. amyloliquefaciens S12, B. subtilis S32, B. subtilis S41, B. amyloliquefaciens S44, B. amyloliquefaciens S45, and B. pumilus S178 using PCR of the ytcP gene and MALDI-TOF. Furthermore, all strains were sensitive to ciprofloxacin, levofloxacin, and rifampicin. Moreover, simultaneous inhibition assays of the Bacillus spp. strains were conducted against STEC serotypes at temperatures of 12°C, 29°C, and 37°C, and at acidic, neutral, and basic pH (37°C). B. pumilus S178 was selected as a candidate strain due to its inhibition of all tested STEC strains at the three evaluated temperatures and pH levels, showing the most significant inhibitory effects compared to the other evaluated strains. In conducting the selectivity, inclusivity, and exclusivity assay, B. pumilus S178 inhibited 100% of the STEC strains it was confronted with, demonstrating a high inhibitory activity in 83.3% of the cases. The inhibitory activity was also assessed against E. coli strains that were not STEC, including diarrheagenic and uropathogenic pathovars of E. coli. The results demonstrated a 100% inhibition rate in this group of strains. \nRegarding non-E. coli strains, only one strain of Salmonella spp. and one strain of Serratia spp. were inhibited, which accounted for 18% of the evaluated strains. \nThe time limit for detecting inhibition was established at 72 hours. In the evaluation of inhibition in minimal media for the peptone water case, where both B. pumilus S178 and the STEC strains showed growth, no inhibition was observed. Moreover, inhibition was more pronounced in fresh cultures, with a higher proportion of vegetative cells. \nWhen evaluating the production of an inhibitory substance in solid medium, early inhibition of the STEC strain was observed in deferred inhibition assays. However, obtaining an inhibitory substance through cultivation in liquid medium and filtration, with or without additional processes like concentration or lyophilization, was not possible. \nThere was also no evidence of B. pumilus S178 blocking the quorum sensing of STEC. \nInhibition was not mediated by a volatile substance. Furthermore, B. pumilus S178 did not activate the lytic cycle of the lambda phage in the evaluated STEC strains, further affirming its safety as a strategy for controlling animal reservoirs of the pathogen. \nThe study of the sporulation process allowed us to establish that sporulation of B. pumilus S178 begins on day 3, reaching its peak spore formation at 7 days in solid medium (89%), and at 8 days in liquid medium (41%). Additionally, a 60-minute lag phase in bacterial growth was observed when B. pumilus S178 was cultivated in brain heart broth and then replicated on tryptone soy broth. The germination process was studied, and it varied depending on the treatment used for spore obtaining, being 40 min when a thermal treatment was applied and 76 min when an alcoholic treatment was used. When evaluating the relationship between germination processes, sporulation processes, and the antagonism observed in STEC strains, it was inferred that due to the brief germination in B. pumilus S178, it may not be associated with the antagonistic effect. \nHowever, a possible relationship with sporulation cannot be ruled out. \nRegarding the safety assessment, B. pumilus S178 was found to be non-pathogenic when orally inoculated in 14-week-old guinea pigs for 7 consecutive days. The animals did not show clinical signs, and no significant differences in body weight were observed between the inoculated and control groups. The qualitative evaluation of the duodenum showed significant differences in favor of the inoculated group regarding mucosal integrity, suggesting a protective effect of the studied strain. Additionally, macroscopic, and microscopic evaluation of the liver and large intestine did not reveal any lesions or lymphoid depletion in the assessment of secondary lymphoid organs. In the quantitative evaluation of the duodenum, no differences were detected, indicating that B. pumilus S178 did not increase the digestive function of the inoculated animals. \nThe inclusion of B. pumilus S178 in silages had no impact on the physical, chemical, and nutritional characteristics of sorghum silage after inoculation with vegetative and spore cultures (total culture) and spore-only cultures. The recovery of microorganisms from the silage was higher in silage inoculated with the total culture. Moreover, compatible strains with the native inoculated strains in both vegetative and spore form were recovered from the silage inoculated with the total culture, which inhibited the EDL 933 strain. This situation was not observed in the silage inoculated with the previously heat-treated culture. \nIn conclusion, B. pumilus S178 shows promise as an adequate pre-slaughter control strategy for STEC due to its inhibitory action on STEC strains and its potential incorporation into sorghum silages, where it is more effective as a total culture.